Epidemiological features of domestic and imported cases with COVID-19 between January 2020 and March 2021 in Taiwan. Issue 39 (1st October 2021) - Wu, Chun-Han; Chou, Yu-Ching; Lin, Fu-Huang; Hsieh, Chi-Jeng; Wu, Ding-Chung; Peng, Chung-Kan; Yu, Chia-Peng
Abstract : Abstract: Coronavirus disease-2019 (COVID-19) is a global pandemic affecting numerous countries around the world. This study elaborates Taiwan's epidemiological characteristics from the 2020 to 2021 COVID-19 pandemic from human, temporal, and geographical dimensions. Big data for cases were obtained from a public database from the Taiwan Centers for Disease Control (CDC) in April 2021. The data were analyzed and used to compare differences, correlations, and trends for human, temporal, and geographical characteristics for imported and domestic COVID-19 cases. During the study period, 1030 cases were confirmed and the mortality rate of 1.0%. The epidemiological features indicated that most cases (953/1030, 92.5%) were imported. A comparison of the domestic confirmed and imported cases revealed the following findings: No significant difference of COVID-19 between males and females for sex was observed; For age, the risk of domestic transmission was significantly lower for 20 to 29 years old, higher for 50 to 59 years old, and >60 years old with odds ratios (ORs) ( P value < .05) of 0.36, 3.37, and 2.50, respectively; For the month of infection, the ORs ( P value < .05) of domestic confirmed cases during January and February 2020 were 22.428; and in terms of area of residence, the ORs ( P value < .05) for domestic confirmed cases in northern and southern Taiwan were 4.473 and 0.033, respectively. Thus, the increase in domestic cases may have been caused by international travelers transmitting the virus in March 2020 and December 2020, respectively. Taiwan has been implementing effective screening and quarantine measures at airports. Moreover, Taiwan has implemented and maintained stringent interventions such as large-scale epidemiological investigation, rapid diagnosis, wearing masks, washing hands frequently, safe social distancing, and prompt clinical classifications for severe patients who were given appropriate medical measures. This is the first report comparing imported and domestic cases of COVID-19 from surveillance data from the Taiwan Centers for Disease Control during January 2020 and March 2021. It illustrates that individuals infected during overseas travel are the main risk factors for the spread of COVID-19 in Taiwan. The study also highlights the importance of longitudinal and geographically extended studies in understanding the implications of COVID-19 transmission for Taiwan's population.